Rights and duties of economic institutions during competition investigations - Zouache, Chouaib (Journal of Human Sciences, 2022)
Competition investigations are launched with the arrival of a notification denouncing the exercise of anti-competitive practices carried out by economic enterprises on a commercial market to the competent authorities, whether administrative, such as the administration in charge of trade or judicial, like the judicial police or the Competition Council. As soon as it is received, they ascertain that the required conditions of quality, interest, , non-prescription and the existence of illegal acts provided for by the competition code have been met. Once the notification has been approved, the commission of inquiry and investigation is made up of reporters from the Council or agents belonging to the tax administration or the administration responsible for trade, officers or agents of the judicial police. It carries out its duties by conducting competition investigations against suspicious institutions, which the law provides that they have certain rights and are bound to a set of duties during these investigations.